Quality Analysis of Local Food Fermented Durian Paste (Tempoyak) in Pontianak Based on Nutrients and Bacterial Contaminants - Hasria Alang; Yuyun Nisaul Khairillah; M. Fiqri Baihaqi; Annisa Nasywa Fahira (Universitas Labuhanbatu, 2024)
Tempoyak is a traditional food resulting from spontaneous fermentation of durian fruit. This fermentation involves the help of LAB which is present naturally. Tempoyak is often found in traditional markets and is a type of ready-to-eat food. The aim of this research is to analyze the feasibility of consuming Tempoyak from several traditional markets in Pontianak based on its nutritional (proximate), antioxidant and microbiological content. Tempoyak sampling was carried out in several traditional markets in Pontianak. The methods used to analyze nutrients are the Kjehdal method, gravimetry and solvent extraction, antioxidants using DPPH, while analyzing microbial pollutants using Standard Plate Count, MPN and qualitative using a specific microbial growth medium by looking at the color indicators formed. The results of the analysis show that the tempoyak circulating in the Pontianak Traditional Market complies with SNI and the number of Coliforms and E. coli in the samples exceeds SNI, the samples do not contain S. aureus and Salmonella contaminants. The results of the analysis show that the tempoyak circulating in the Pontianak Traditional Market complies with SNI based on its nutritional and antioxidant content, and the number of Coliforms and E. coli in the samples exceeds the SNI so it is not suitable for consumption, even though the samples do not contain S. aureus and Salmonella contaminants